Cross-Cultural Networking: Translators in the French-German Network of Petites Revues at the End of the Nineteenth Century - Pym, Anthony (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractA network of small literary periodicals distributed the principles of Paris-based Aestheticism throughout the industrialized world at the end of the nineteenth century. These publications formed clear links across national borders, and those links were often manifested as translations that helped disseminate knowledge and form a sense of artistic belonging. However, the relations within the network could also be actively negative, as various receptive strategies used translations and commentaries to defend national rather than international aesthetics. In periods of political tension between France and Germany, such relations were further complicated by use of a wider intercultural space. From 1871, cross-cultural links in the network significantly drew on intermediaries from Belgium, Holland, Alsace and Switzerland, cultural spaces between the main centers of the French-German network. A more centralized desire for intercultural space was nevertheless manifested in 1895, when the Mercure de France and the Neue deutsche Rundschau jointly organized questionnaire surveys of the cultural relations between France and Germany. The strategic use of intercultural space in these circumstances can be shown by following the translations into French of Wagner and Nietzsche, which could have extended the network and increased cross-cultural understanding. By the end of the century, however, most of the potentially affirmative relations had unraveled and intermediaries began to take sides. The points of contact in the network, including the translators and translations, began to mark out differences rather than extensions, as Europe tilted toward the wars of the twentieth century.